Formation of BaCrO4 nano crystallites within thermally evaporated sodium bis-2-ethylhexyl-sulfosuccinate and stearic acid thin films - Rautaray, D.; Sinha, K.; Sainkar, S. R.; Pasricha, R.; Pavaskar, N. R.; Sastry, M. (Journal of the American Ceramic Society, 2005)
This paper describes the growth of barium chromate (BaCrO4) nanocrystallites within thermally evaporated thin films of stearic acid (StA) and sodium bis-2-ethylhexyl-sulfosuccinate by a process of Ba2+ ion entrapment followed by in situ reaction CrO42- ions. Dense spherical assemblies of BaCrO4 nanocrystallites of very uniform size (similar to50 nm) were obtained within the two different host matrices. The spherical assemblies were composed of smaller (ca. 5-10 nm size) BaCrO4 crystals indicating that efficient size control over crystal size may be exercised by the matrix. Contact angle measurements of the BaCrO4-StA and BaCrO4-sodium bis-2-ethylhexyl-sulfosuccinate films indicated that they were hydrophobic, thus pointing to the possible role of hydrophobic interaction between the StA and sodium bis-2-ethylhexyl-sulfosuccinate monolayer-covered BaCrO4 crystals in the assembly process.